Determinants of sovereign borrowing choices in Sub-Saharan Africa - Lehasa, Mecha (Graduate School of Business (GSB), 2021)
There is a growing and legitimate concern about sovereign debt increasing to unsustainable levels among the Sub-Saharan African (SSA) countries. Understanding the determinants of external debt to these countries influenced the direction of this study. The existing literature that was examined shed light mostly on the qualitative determinants of sovereign borrowing. In addition to existing empirical literature, there is a complimentary need to examine further the quantitative determinants of external debt. The researcher seeks to establish the extent to which the cost of borrowing (proxied by interest rate) explains the changes in the borrowing behaviour (proxied by external debt) among SSA countries. To achieve this objective, data from 36 SSA countries for the period 2009–2017 was used. The data were collected from International Debt Statistics compiled by the World Bank. External debt has been regressed against interest rate and other predictor variables. Hausman tests, robustness tests and collinearity tests were carried out to ascertain the validity of results. Interest rate is found to have a positive determining impact on external debt for all SSA countries aggregated: SSA countries excluding South Africa (SA); SSA excluding Nigeria; SSA excluding Nigeria and SA; SSA excluding debt-distressed countries, middle income and oilexporting countries. It does not have predictive power over changes in external debt for SSA excluding countries at high risk of distress; countries with low to moderate risk of distress; heavily indebted poor countries (HIPC) initiative post-implementation recipient countries; low income, other resource intensive and non-resource-intensive countries. External debt is also found to respond to changes in: gross national income (GNI); exports-to-imports ratio; primary income on foreign direct investment (FDI); reserves-to-imports ratio; FDI-to-GNI ratio; debt service-to-GNI ratio; interest arrears on long-term debt; short-term-to-total-debt ratio; and reserves-to-debt ratio for different country groupings. Different country groupings are found to have unique combinations of external debt determinants.